Stroboscope Based Synchronization of Full Frame CCD Sensors - Liang Shen; Xiaobing Feng; Yuan Zhang; Min Shi; Dengming Zhu; Zhaoqi Wang (Sensors, 2017)
The key obstacle to the use of consumer cameras in computer vision and computer graphics applications is the lack of synchronization hardware. We present a stroboscope based synchronization approach for the charge-coupled device (CCD) consumer cameras. The synchronization is realized by first aligning the frames from different video sequences based on the smear dots of the stroboscope, and then matching the sequences using a hidden Markov model. Compared with current synchronized capture equipment, the proposed approach greatly reduces the cost by using inexpensive CCD cameras and one stroboscope. The results show that our method could reach a high accuracy much better than the frame-level synchronization of traditional software methods.